1967
DOI: 10.1037/h0024139
|View full text |Cite
|
Sign up to set email alerts
|

A primacy effect in subjective probability revision.

Abstract: 2 experiments presented Ss with sequences of data that 1st favored 1 hypothesis, and then changed to favor a 2nd hypothesis. After each datum Ss became more or less sure of which hypothesis was correct. They reflected this change of opinion with probability estimates, which were compared with probabilities calculated by means of Bayes's theorem. Estimated probabilities changed from favoring the 1st hypothesis to favoring the 2nd hypothesis later than did corresponding Bayesian probabilities. Data that occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
42
0

Year Published

1968
1968
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(43 citation statements)
references
References 8 publications
1
42
0
Order By: Relevance
“…For example, DuCharme (1970) argued that subjects were biased against making responses that appear extreme on the response scale used. This paper describes an experiment directed at investigating the formally irrelevant aspects of sample order and method of presentation.With regard to order, primacy has been reported by Peterson and DuCharme (1967) and by Dale (1968) while Pitz and Reinhold (1968) and Shanteau (1970) have found recency . Slovic and Lichtenstein (1971) argue that which effect occurs could depend on the form of the sample data.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…For example, DuCharme (1970) argued that subjects were biased against making responses that appear extreme on the response scale used. This paper describes an experiment directed at investigating the formally irrelevant aspects of sample order and method of presentation.With regard to order, primacy has been reported by Peterson and DuCharme (1967) and by Dale (1968) while Pitz and Reinhold (1968) and Shanteau (1970) have found recency . Slovic and Lichtenstein (1971) argue that which effect occurs could depend on the form of the sample data.…”
mentioning
confidence: 98%
“…With regard to order, primacy has been reported by Peterson and DuCharme (1967) and by Dale (1968) while Pitz and Reinhold (1968) and Shanteau (1970) have found recency . Slovic and Lichtenstein (1971) argue that which effect occurs could depend on the form of the sample data.…”
mentioning
confidence: 98%
“…The estimates were more conservative for extreme probabilities relative to the correct Bayesian probability, but there were no major differences between the final estimates of subjects making sequential estimates (as the cards were drawn) versus those making a single, final estimate. Peterson and DuCharme (1967), using dice and colored chips found that sequential estimates tended to be slow to follow the correct Bayesian values, with estimates less resistant to moving up (towards 100%) than down. Finally, in an experiment not involving estimating probabilities, Bruner and Potter (1964) studied subjects' ability to recognize pictures of common objects that gradually came into focus.…”
mentioning
confidence: 99%
“…If Bayes' theorem is to be an acceptable model of human inference, then these variables should not markedly influence human inference. For example, it has been shown that while Bayes' theorem is indifferent to the order in which the conditionally independent data occur, human behavior does reflect this factor (Peterson & DuCharme, 1967). The present study is concerned with another in this class of variables: the a priori probability of the event or datum on the basis of which inference is made-usually designated P(D).…”
mentioning
confidence: 99%